Analisis Retorika dalam Ta'kid Al-Madh dan Al-Dzamm: Seni Menyampaikan Makna Pujian dan Celaan - Maulana, Arjuna Dwi; Aulia, Ashrafah Alaifhi; Putri, Bella Tiara; Al Rasyid, Harun (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to examine the application of the rhetorical techniques of Ta'kid Al-Madh Bima Yusybih Al-Dzamm and Ta'kid Al-Dzamm Bima Yusybih Al-Madh in conveying the meaning of praise and blame, with a focus on its use in the Qur'an as an example main. The aim of this research is to reveal how these two forms of rhetoric function in deepening meaning and their impact on reader understanding. This research focuses on the application of these techniques in the verses of the Koran to see their role in enriching the moral and spiritual message. The method used is a descriptive qualitative approach, by analyzing verses from the Koran which contain examples of the application of these two techniques. The research results show that these two rhetorical techniques not only enhance language structure, but also increase in-depth understanding of the message to be conveyed, whether in the form of praise or blame. Overall, the conclusion of this research shows that Ta'kid Al-Madh and Ta'kid Al-Dzamm in the Al-Qur'an play an important role in strengthening the message and motivating readers to better understand the moral values contained therein.